63x-7=7(9x-1)

Simple and best practice solution for 63x-7=7(9x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 63x-7=7(9x-1) equation:



63x-7=7(9x-1)
We move all terms to the left:
63x-7-(7(9x-1))=0
We calculate terms in parentheses: -(7(9x-1)), so:
7(9x-1)
We multiply parentheses
63x-7
Back to the equation:
-(63x-7)
We get rid of parentheses
63x-63x+7-7=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| n/11=10 | | 6x+15=4x+49 | | –10(x–3)=10 | | 4w+4-2w=2w+18-2w | | 4x^2+5x=4096 | | 10c^2=E | | q+57=95 | | (3x-2)^2=32 | | 2g+14=3g+2-g+12 | | 1=14+b | | 22+4x+90=90 | | 6s-4=8(2+1/4⁸) | | 2a+7=-9+4a | | 35=15-r | | 1/5x=3=7 | | 8x+1=12x+4 | | x-1.5=-4.5 | | 25+3x=3x+25 | | j−747=3 | | 104+33=5x+13 | | 0x+1=5x+9 | | 20x+79=20x+9 | | s4−8=12 | | –8(t–16)=8 | | n−45=14 | | v/10=11/17 | | 12–3x=4+5x | | 11x+5=21x-5 | | 2x=6=96 | | 3y-7y=-18 | | -g-8g=36 | | x/16=-3 |

Equations solver categories